System of equations

Algebra Level 5

{ 1 x + 1 y = 9 ( 1 x 3 + 1 y 3 ) ( 1 + 1 x 3 ) ( 1 + 1 y 3 ) = 18 \large \begin{cases} \dfrac 1x+\dfrac 1y =9 \\ \left(\dfrac 1{\sqrt[3]x} + \dfrac 1{\sqrt[3]y}\right) \left(1+ \dfrac 1{\sqrt[3]x}\right)\left(1+ \dfrac 1{\sqrt[3]y}\right)=18 \end{cases}

Find the sum of all the distinct possible values of x + y x+y , where x x and y y are real numbers.


The answer is 1.125.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let 1 x 3 = a \frac{1}{\sqrt[3]{x}}=a and 1 y 3 = b \frac{1}{\sqrt[3]{y}}=b , then the system of equations become:

a 3 + b 3 = 9 ( a + b ) 3 3 a b ( a + b ) = 9 a^3+b^3=9 \implies \left(a+b\right)^3-3ab\left(a+b\right)=9

( a + b ) ( 1 + a ) ( 1 + b ) = 18 ( a + b ) ( 1 + ( a + b ) + a b ) = 18 \left(a+b\right)\left(1+a\right)\left(1+b\right)=18 \implies \left(a+b\right)\left(1+\left(a+b\right)+ab\right)=18

Let a + b = c a+b=c and a b = d ab=d , then the system of equations reduce to:

c 3 3 c d = 9 c^3-3cd=9 (I) and c ( 1 + c + d ) = 18 c + c 2 + c d = 18 3 c + 3 c 2 + 3 c d = 54 c\left(1+c+d\right)=18 \implies c+c^2+cd=18 \implies 3c+3c^2+3cd=54 (II)

Adding (I) and (II) :

c 3 + 3 c 2 + 3 c = 63 c 3 + 3 c 2 + 3 c + 1 = 64 ( c + 1 ) 3 = 64 c + 1 = 4 c = 3 a + b = 3 c^3+3c^2+3c=63 \implies c^3+3c^2+3c+1=64 \implies \left(c+1\right)^3=64 \implies c+1 = 4 \implies \boxed{c=3} \implies \boxed{a+b=3}

Substituting c = 3 c = 3 in (I) , we have d = 2 a b = 2 \boxed{d=2} \implies \boxed{ab=2} .

Solving a + b = 3 a+b=3 and a b = 2 ab=2 , we have a = 1 a=1 , b = 2 b=2 or b = 1 b=1 , a = 2 a=2 .

Which means that 1 x 3 = 1 \frac{1}{\sqrt[3]{x}}=1 , 1 y 3 = 2 \frac{1}{\sqrt[3]{y}}=2 or 1 y 3 = 1 \frac{1}{\sqrt[3]{y}}=1 , 1 x 3 = 2 \frac{1}{\sqrt[3]{x}}=2 .

Subsequently, x = 1 x = 1 , y = 1 8 y=\frac{1}{8} or y = 1 y=1 , x = 1 8 x=\frac{1}{8} .

Therefore, x + y = 9 8 = 1.125 x+y = \frac{9}{8} = \boxed{1.125} in either case.

Using the identity

( a + b + c ) 3 = a 3 + b 3 + c 3 + 3 ( a + b ) ( b + c ) ( c + a ) (a+b+c)^3=a^3+b^3+c^3+3(a+b)(b+c)(c+a)

( 1 x \leftroot 1 \uproot 2 3 + 1 y \leftroot 1 \uproot 2 3 + 1 ) 3 = 1 x + 1 y + 1 + 3 ( 1 x \leftroot 1 \uproot 2 3 + 1 y \leftroot 1 \uproot 2 3 ) ( 1 y \leftroot 1 \uproot 2 3 + 1 ) ( 1 + 1 x \leftroot 1 \uproot 2 3 ) = 9 + 1 + 3 ( 18 ) = 10 + 54 = 64 \left(\dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{x}\qquad}+\dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{y}}+1\right)^3=\dfrac{1}{x}+\dfrac{1}{y}+1+3\left(\dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{x}}+\dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{y}}\right)\left(\dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{y}}+1\right)\left(1+\dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{x}}\right)=9+1+3(18)=10+54=64

Hence,

1 x \leftroot 1 \uproot 2 3 + 1 y \leftroot 1 \uproot 2 3 + 1 = 4 \dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{x}} + \dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{y}} + 1=4

It follows that

1 x \leftroot 1 \uproot 2 3 + 1 y \leftroot 1 \uproot 2 3 = 3 \dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{x}} + \dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{y}} =3

The system is now reduced to

1 x + 1 y = 9 \dfrac{1}{x}+\dfrac{1}{y}=9

1 x \leftroot 1 \uproot 2 3 + 1 y \leftroot 1 \uproot 2 3 = 3 \dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{x}} + \dfrac{1}{\sqrt[\leftroot{-1}\uproot{2}\scriptstyle 3]{y}} =3

Which is a symmetric system, having the solution

x = 1 8 , y = 1 x=\dfrac{1}{8},y=1 and x = 1 , y = 1 8 x=1,y=\dfrac{1}{8}

Finally,

x + y = 1 8 + 1 = 9 8 = x+y=\dfrac{1}{8}+1=\dfrac{9}{8}= 1.125 \color{#D61F06}\large \boxed{1.125}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...